Preparation of NIR-responsive, ROS-generating and antibacterial black phosphorus quantum dots for promoting the MRSA-infected wound healing in diabetic rats. (1st January 2022) - Huang, Shuocheng; Xu, Shibo; Hu, Yanan; Zhao, Xingjun; Chang, Linna; Chen, Zhenhua; Mei, Xifan
Abstract: Multidrug-resistant (MDR) bacteria-induced infection is becoming a huge challenge for clinical treatment, especially for non-healing diabetic wound infections, which increase patient mortality. MRSA infections and delayed wound healing (methicillin-resistant Staphylococcus aureus) accounted for a higher proportion. Although surgical debridement and continuous use of antibiotics are still the main clinical treatments, new multifunctional therapeutic nanoplatform are attractive for MIDW. Thus, in the present study, black phosphorus quantum dots (BPQDs) encapsulated in hydrogel (BPQDs@NH) were utilized as nanoplatforms for MIDW treatment to achieve the multifunctional properties of NIR (near infrared) responsiveness, ROS (reactive oxygen species) generation and antibacterial activity. Upon NIR irradiation, the temperature of the BPQDs@NH-treated MIDW area rapidly increased up to 55 °C for sterilization. In vitro experiments showed that BPQDs@NH exerted a synergistic effect on inhibiting MRSA by producing of ROS, lipid peroxidation, glutathione, adenosine triphosphate accumulation and bacterial membrane destruction upon NIR irradiation. The resulting BPQDs@NH achieved an effective sterilization rate of approximately 90% for MRSA. Furthermore, animal experiments revealed that BPQDs@NH achieved an effective closure rate of 95% for MIDW after 12 days by reducing the inflammatory response and regulating the expression of vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (bFGF). Meanwhile, intravenous circulation experiments showed good biocompatibility of BPQDs, and no obvious damage to rat major organs was observed. The obtained results indicated that BPQDs@NH achieved the synergistic functions of NIR-responsiveness, ROS generation, and antibacterial activity and promoted wound healing, suggesting that they are promising multifunctional nanoplatforms for MIDW healing. Statement of significance: 1. NIR-triggered ROS-generating and antibacterial nanoplatforms are attractive in the wound healing field. 2. In this work, black phosphorus quantum dots encapsulated in a hydrogel were used as a nanoplatform for treating MRSA infected wounds. 3. The obtained materials have achieved an effective sterilization rate for MRSA and effective wound closure rate. Graphical abstract: Image, graphical abstract